2010
DOI: 10.1111/j.1757-7861.2010.00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of paraspinal muscle injury in one‐level lumbar posterior inter‐body fusion: modified minimally invasive and traditional open approaches

Abstract: Compared with TOPA, MMIA can significantly lessen paraspinal muscle injury, and reduce the incidence of low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
73
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 22 publications
4
73
1
Order By: Relevance
“…Although this was not significant in the present study, the small sample size may mask the true difference. Postoperative MRI also found increased T 2 signal intensity ratio of the multifidus to psoas (control) muscle, similar to a prior study that also found greater changes in the open fusion group as compared to minimally invasive posterior interbody fusion [30]. The present study found only an insignificant trend for greater MRI muscle change with the more invasive pedicle screw approach.…”
Section: Discussionsupporting
confidence: 88%
“…Although this was not significant in the present study, the small sample size may mask the true difference. Postoperative MRI also found increased T 2 signal intensity ratio of the multifidus to psoas (control) muscle, similar to a prior study that also found greater changes in the open fusion group as compared to minimally invasive posterior interbody fusion [30]. The present study found only an insignificant trend for greater MRI muscle change with the more invasive pedicle screw approach.…”
Section: Discussionsupporting
confidence: 88%
“…There are many other studies that demonstrate much greater injury to the surrounding tissues with a midline approach. 6,15 This is possibly the start of the cascade that leads to a greater incidence of adjacent segment pathology with the midline approach, which our data support. Also, a more lateral pedicle screw entry point has a much lower incidence of violating the adjacent facet and capsule of the caudal level.…”
Section: Discussionsupporting
confidence: 78%
“…1,20,[23][24][25] As a result, surgeons are examining options to reduce surgical site infection, and in doing so have revisited the utility of the Wiltse paraspinal approach as a potential alternative to minimizing wound complications in this high-risk group of patients. 2,3,6,8,11,16 aBBreViatiOnS BMP = bone morphogenetic protein; SSII = spine surgical invasiveness index. OBJectiVe The objective of this study was to determine if there is a significant difference in surgical site infection (SSI) when comparing the Wiltse and midline approaches for posterior instrumented interbody fusions of the lumbar spine and, secondarily, to evaluate if the reoperation rates and specific causes for reoperation were similar for both approaches.…”
mentioning
confidence: 99%
“…PLIF allows reliable neurological decompression, satisfactory interbody fusion and disc height restoration [74]. Potential disadvantages [74,75], however, may be substantial paraspinal damage linked to long-term muscle retraction, battered root syndrome, and limited ability to achieve adequate lordosis consistently [73][74][75].…”
Section: Plifmentioning
confidence: 99%
“…Initially, the PLIF method is a conventional lumbar approach in which most spinal surgeons are well-skilled and experienced. A posterior access allows outstanding visualization of the nerve roots deprived of affecting blood supply to the graft [72,73]. PLIF allows reliable neurological decompression, satisfactory interbody fusion and disc height restoration [74].…”
Section: Plifmentioning
confidence: 99%